Successful double valve replacement in a pregnant woman with refractory heart failure due to early dysfunction of the biological prosthesis in the aortic valve position - José C Candia; José F Alderete; Jorge Martínez; Oscar A Lovera; Jorge Jarolín; Osmar Antonio Centurión (Global Journal of Medical and Clinical Case Reports - Peertechz Publications, 2019)
Rheumatic fever continues to be a frequent cause of cardiac valve disease in developing countries. The combination of rheumatic heart disease and pregnancy represents a challenge in the management of these patients. Prevention strategies are often insufficient; this is why we continue to observe complicated cases that demand more complex treatments. We are reporting the case of a 20-year-old woman, with a history of aortic valve replacement and mitral valve repair due to rheumatic heart disease. Two years later after her valve replacement, she attended consultation with signs and symptoms of heart failure in functional class III during a pregnancy of 20 weeks. The echocardiography showed: dysfunctional biological aortic prosthesis with severe stenosis and moderate regurgitation (central and para-valve leak), as well as severe mitral valve insufficiency, eccentric, directed towards the atrial free wall. She was admitted, and received optimal medical treatment for 4 weeks with little response and subsequent worsening. A multidisciplinary committee was formed including cardiologists, cardiac surgeons, obstetricians, neonatologists, and specialists in bioethics. It was decided to proceed with valve replacement surgery during the 21st week of her gestation. Successful double valve replacement (mitral and aortic) was performed, without complications for the patient or the fetus. She was discharged in good health. In her 38th week of gestation, a successful cesarean delivery was performed without any complications.